End of World War II: Truth and Lie of History - E. G. Bahdanovich; D. A. Kozel (Наука и техника)
The paper analyzes the main events of the last period of the World War II. A special attention is paid to the feat of the Soviet Armed Forces, that defeated the Kwantun Army in August 1945 and precipitated an unconditional capitulation of Japan and brought freedom to the peoples of Asia. The paper also reveals tragic consequences of atomic bombings of Hiroshima and Nagasaki. The authors emphasize a key role of the Soviet Union in victorious completion of the World War II.